Dynamic-interfacial properties of dodecyl-Î²-D-maltoside and Dodecyl-Î²-D-fructofuranosyl-Î±-D-glucopyranoside at Dodecane/Water Interface - Niraula, B.B.; Chun, T.K.; Othman, H.; Misran, Misni (Elsevier, 2004)
Interfacial properties of dodecyl-Î²-d-maltoside (DDM) and dodecyl-Î²-d-fructofuranosyl-Î±-d-glucopyranoside (DFG) are being explored at both the air/water and dodecane/water interfaces. While surface tensiometry was employed for the study of the air/water interface, the dynamic drop volume technique was used to explore the oil/water (o/w) interface. Both surfactants are water soluble and non-ionic in nature. These surfactants differ slightly in their head group composition, whereas the structure of their alkyl tail is identical with same number of CH 2 groups in it. Therefore they differ slightly in head group polarity, and therewith in HLB (hydrophilic-lipophillic balance) value. This difference in HLB value of these surfactants is strongly reflected in their surface and interfacial properties, for the same bulk surfactant concentration DDM with less polar head group and HLB value of 13.35 showed a slightly greater degree of surface and interfacial tension reduction compared to DFG with HLB value of 13.5. This small difference in head group polarity is not only reflected in difference in critical micelle concentration (cmc) and surface tension reduction at cmc, but it is strongly manifested in both the dynamic and equilibrium interfacial tension profiles of these surfactants. Since the hydrophobic tail of both surfactants is same, it is evident that head group polarity (HLB value) of these surfactants played a great role in both the surface and interfacial tension reduction (adsorption at the surface and at oil/water interface), and therewith in adsorption kinetics and rate of diffusion from the bulk solution to the liquid-liquid interface. Since the equilibrium interfacial tension-log concentration Î³ eq - Î³ 0(log C) profiles of these surfactants did not show any depression in interfacial tension at the neighborhood of cmc and since the interfacial pressure-log concentration dÏ(d log C) profiles of these surfactants shows a linear relation with a regression coefficient exceeding 0.99, it is assumed that both surfactants were relatively free from surface-active impurities in accordance to Lunkenheimer. Since the bulk concentration tested here exceeded cmc in both case, the equilibrium interfacial tension versus concentration profiles of these surfactants were evaluated using Langmuir-Szyszkowski type isotherm. Also, the ÎGcmc0 value of these surfactants is much higher than their ÎGad0 value, the fact that enables us to assume that the adsorption is favored over micellization. As far as diffusion coefficient (D) is concerned, the D of these surfactants decreased with increasing bulk concentration, suggesting that kinetics effects are probably beginning to compete with diffusion-controlled transport mechanism. This suggests that diffusion-controlled mechanism alone cannot fully describe the transport of surfactant mass from the bulk solution into the o/w interface, and that the diffusion-controlled mass transport mechanism is probably kinetically hindered. While the D decreased with bulk surfactant concentration in both cases, the less polar DDM showed a slightly smaller D compared to DFG, implying that as an emulsifying agent the former glycolipid would perform slightly better than the latter. The D of both the DDM and DFG was calculated to be of the order of 10 -10 m 2/s, suggesting that emulsifying property of these surfactants is comparable to most commercially available non-ionic surfactants. The magnitude of D further indicate that adsorption kinetics of these surfactants from the subsurface to the given o/w interface is slow, which in turn suggests that adsorption of these surfactant at the given o/w interface is cooperative, that as emulsifying agents these surfactants can perform as good as most commercially available surfactants.